Enhancing Organizational Resilience Through Strengthening Knowledge Management, Adversity Intelligence and Work Motivation - Uli Rohana Siregar; Andi Hermawan (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Organizational resilience is a process carried out by organizational leaders in overcoming difficult situations by issuing appropriate policies and mobilizing all components of the organization and reformulating concrete positive steps in a short time so that the organization does not experience shocks and the organization's operational activities can run as they should. Educational institutions managed by the community as educational organizations face extraordinary challenges in the competition to survive and the slow pace of development due to educational policies. Consequently, research is essential to gather data on factors associated with enhancing organizational resilience. This study seeks to identify strategies, methodologies, and best solutions to enhance organizational resilience via knowledge management, adversity intelligence, and job motivation. This research use a survey methodology combined with path analysis and the SITOREM technique to evaluate critical indicators. Employing Smart PLS analysis to ascertain the extent of the impact among the variables of knowledge management, adversity intelligence, and job motivation on organizational resilience. The SITOREM analysis yields an ideal approach for enhancing organizational resilience. This study offers recommendations for enhancing organizational resilience, serving as a reference for strategic decision-making for school principals, the Education Office, and the Ministry of Education.